PENGARUH KINERJA LINGKUNGAN TERHADAP RETURN ON ASSETS DAN RETURN ON SALES PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2011 - YUNIAR P, RIZKY Yuniar (Jurnal Akuntansi AKUNESA, 2013)
This purpose of this research to know influence performance environmental of theReturn On Assets and Return On Sales. In this research measured environmentalperformance using the PROPER while profitability using ROA and ROS. To take the sampleusing Purposive sampling method. The company which became the sample is 6 companieswhich listed on Bursa Efek Indonesia (BEI). This research using Structural EquationModeling analysis (SEM) by approach Partial Least Square (PLS). This research resultindicates that environmental performance influential negative to ROA and ROS.Keywords: PROPER, Return On Assets, Return On Sales